Impact of 3D cell culture hydrogels derived from basement membrane extracts or nanofibrillar cellulose on CAR-T cell activation - Sonia Aristin Revilla; Alessandro Cutilli; Eugenia Cambiaso; Dedeke Rockx-Brouwer; Cynthia Lisanne Frederiks; Marc Falandt; Riccardo Levato; Onno Kranenburg; Caroline A. Lindemans; Paul James Coffer; Victor Peperzak; Enric Mocholi; et al. (iScience)
Summary: Hydrogel-based 3D culture systems are increasingly used for preclinical evaluation of cell-based immunotherapies, including chimeric antigen receptor T (CAR-T) cells. However, hydrogel properties can influence T cell behavior, potentially affecting interpretation of immunotherapy studies. We assessed CD4+ T and CAR-T cell responses in two chemically undefined matrices—Matrigel and basement membrane extract (BME)— and in a synthetic nanofibrillar cellulose (NFC) hydrogel. Although NFC was mechanically stiffer, T cell activation and proliferation were higher in NFC than in Matrigel or BME. Murine CD4+ T cells acquired a regulatory phenotype in Matrigel and BME but not in NFC. Similarly, CAR-T cell function was reduced in Matrigel and BME but maintained in NFC. These findings underscore how matrix composition can shape T cell responses in 3D culture. NFC provides a chemically defined alternative that preserves T cell activity, supporting its use in more accurate preclinical testing of immunotherapies.